STRATEGI MARKETING INFLUENCER PADA PRODUK WARDAH DALAM MENINGKATKAN BRAND AWARENESS MELALUI INSTAGRAM - Tri Yunianto, Mifta Aulia Venturini (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
The research to be conducted is aware that there is so much competition between businesses in the increasingly tight digital era in showing efforts to build marketing strategies to compete. As, the existence of a company requires building a strategy to increase the potential for brand awareness, efforts to promote a product in consumer trust. Various strategies that are important to grow a brand in the rapidly growing digital era, for activities in marketing marketing strategies. As an efficient digital marketing platform channel in online advertising to target consumers towards a brand they trust, by involving influencer marketing in a greater influence to reach consumers and have a greater influence, especially on social media. By strengthening a brand itself in increasing brand awareness of the wider community. The strategy used by wardahbeauty.jogja through Instagram to increase brand awareness, especially in the wider community, with the implementation of influencer marketing, it can be shown that the strategy carried out by wardahbeauty.jogja has successfully implemented influencer marketing, by collaborating through influencers on Instagram from the role of the public and targets that are in accordance with wardahbeauty.jogja. The method to be used in this study is descriptive qualitative by conducting interview sessions and participant observation. As researchers will use influencer marketing strategies, with the involvement of influencers on Instagram in consumer targets that are in accordance with Wardah products, brand awareness will increase.